Notch signaling dynamically regulates adult β cell proliferation and maturity - Bartolome, Alberto; Zhu, Changyu; Sussel, Lori; Pajvani, Utpal B. (The Journal of Clinical Investigation, 2018)
Notch signaling regulates differentiation of the pancreatic endocrine lineage during embryogenesis, but the role of Notch in mature β cells is unclear. We found that islets derived from lean mice show modest β cell Notch activity, which increases in obesity and in response to high glucose. This response appeared maladaptive, as mice with β cell–specific–deficient Notch transcriptional activity showed improved glucose tolerance when subjected to high-fat diet feeding. Conversely, mice with β cell–specific Notch gain of function (β-NICD) had a progressive loss of β cell maturity, due to proteasomal degradation of MafA, leading to impaired glucose-stimulated insulin secretion and glucose intolerance with aging or obesity. Surprisingly, Notch-active β cells had increased proliferative capacity, leading to increased but dysfunctional β cell mass. These studies demonstrate a dynamic role for Notch in developed β cells for simultaneously regulating β cell function and proliferation.